Spontaneous Spleen Rupture in a Teenager: An Uncommon Cause of Acute Abdomen - Verroiotou Maria; Al Mogrampi Saad; Ioannis Fardellas (Case Reports in Medicine)
Spontaneous spleen rupture is a rare complication of infectious diseases and it can become a potentially life-threatening condition if not diagnosed in time. A 17-year-old Greek female presented to the ER due to acute abdominal pain, mainly of the left upper quadrant. She had no recent report of trauma. The patient was pale, her blood pressure was 90/70 mmHg, and her pulse was 120 b/min. Clinical examination of the abdomen revealed muscle contraction and resistance. The patient was submitted to an ultrasound of the upper abdomen and to a CT scanning of the abdomen that revealed an extended intraperitoneal hemorrhage due to spleen rupture. Due to the patient’s hemodynamic instability, she was taken to the operation room and splenectomy was performed. Following a series of laboratory examinations, the patient was diagnosed to be positive for current cytomegalovirus infection. The postoperative course was uneventful, and in a two year follow-up the patient is symptom-free. Spontaneous spleen rupture due to Cytomegalovirus infection is a rare clinical entity, described in few case reports in the world literature and should always be taken into consideration in differential diagnosis of acute abdomen, especially in adolescents with no recent report of trauma.